Shear resistance improvement of oil-contaminated ballast layer with rubber shred inclusions - Chan, Chee Ming; S.M Johan, Siti Farhanah (Geotec., Const. Mat. & Env., 2016)
Railway ballast, which form an integral part of rail tracks, is highly susceptible to subsistence due to both vibration transmitted by the passing trains, as well as the breakage of ballasts with repeated impact. The resulting subsistence necessitates regular monitoring and maintenance, involving cost- and time- consuming remedial actions, such as stone-blowing and ballast renewal. Measures to minimize the wear and tear effect are therefore desirable to prolong the lifespan of the ballast layer. It is even more critical when the ballast is contaminated with oil and grease from braking wheels and leakages. This paper describes the inclusion of rubber shreds (≤10 mm in length, 1.5 mm thick) derived from the inner tubes of motorcycle tyres in oil-contaminated ballast layer for shear resistance improvement. The tests are mainly carried out in a standard direct shear test setup, i.e. shear box measuring 60 mm x 60 mm. Granitic stones of suitable sizes were sieved and used as representative samples of typical ballast. The samples were soaked in lubricant oil for 14 days to simulate the contamination. The direct shear test results indicated rubber shreds inclusion could effectively improve the shear resistance of ballast and expedient in deformation control with increased ductility of the composites. This could potentially improve absorption of impact, hence reduction of breakages of the ballasts. Clearly both mechanisms contribute to the overall reduced subsistence, accompanied by an increase in the shear resistance. However, further investigations in a dynamic test setup are necessary for verifications prior to field implementation.